Validity and reliability of Malay breast cancer awareness scale for male to female transgender - Md Zin, Hezlin; Draman, Samsul; Shalihin, Mohd Shaiful Ehsan; Mohd Rus, Razman (IIUM Press, 2022)
The breast cancer risk among female transgender for those who are using hormonal therapy are emerging. Majority of them also engaged in breast implant procedure as resemblance of female sexual characteristic and satisfaction, without realizing the risk of cancer development. Thus, breast cancer risk assessment of female transgender in Malaysia should be further evaluated. This study aims to develop and validate an assessment tool in Malay version to measure breast cancer awareness among female transgender in Malaysia. A cross sectional study with a purposive sampling method was conducted among 300 respondents in Pahang, Kedah and Kelantan. The minimum respondents required was 300 persons based on the Nunnally method, with ratio of item, 1: 10. All the subjects were given the questionnaires on sociodemographic data and breast cancer related items which consists of five domains. They are the knowledge of symptoms and clinical features; knowledge of risk factors for breast cancer; knowledge of breast screening programmes; barriers in seeking medical help and lastly the confidence, skills and behaviour in relation to breast selfexamination. Each domain consists of five to seven items. All the questions’ responses are recorded as ‘Yes’, ‘No’ or ‘Not Sure’ response. Reliability was determined using Cronbach’s alpha for internal consistency while construct validity was assessed using exploratory factor analysis. The reliability of this 28 items questionnaire was 0.864 with five meaningful domains as highlighted. In conclusion, this scale is valid and reliable.